Manual of Oculoplastic Surgery (Springer International Publishing, 2018)
For the last two decades, this best-selling, step-by-step guide to oculoplastic surgery has been highly respected and widely used by ophthalmologists, oculofacial plastic fellows, residents, ENT-facial plastic surgeons, and general plastic surgeons. The revised and updated fifth edition of Manual of Oculoplastic Surgery is designed to guide the physician in exploring and completing a variety of ocular plastic procedures in a comprehensive and logical step-by-step sequence. It features new authors. Sections include: Trauma, Lacrimal Surgery, Cosmetic, Congenital Ptosis, Acquired Ptosis, Eyelid Malposition, Facial Nerve Dysfunction, Eyelid Flaps, Orbital Surgery, and Therapeutic Considerations. Each procedure in this must-have resource includes a review of the surgical anatomy, step-by-step instructions, plus the book is complete with more than one hundred color illustrations and dozens of surgical videos for further education.